AB0330 Long-term administration of tocilizumab increases the structural remission rate year by year and continuously inhibits radiographic progression: 3 year results from michinoku tocilizumab study group. (23rd January 2014) - Watanabe, R.; Okuno, H.; Ishii, T.; Harigae, H.; Hirabayashi, Y.
Abstract : Background: The inhibition of radiographic progression is one of the important therapeutic goals in patients with rheumatoid arthritis (RA). Tocilizumab (TCZ) is a humanized anti-human IL-6 receptor antibody and it has been reported that it effectively inhibits radiographic progression over 1 year. However, there are few reports about efficacy of longer term administration. Objectives: The aim of this study is to assess the long-term efficacy of treatment with TCZ on radiographic progression in patients with RA under routine clinical practice. Methods: The Michinoku Tocilizumab Study Group comprises 34 institutions in the Northeast region of Japan. RA patients who received 8 mg/kg TCZ every 4 weeks were registered between June 2008 and December 2010 [1 ]. Among them, the clinical and structural outcomes were evaluated in 130 patients who passed over 1 year including 50 patients who passed over 3 years. Results: At baseline, the mean age of 130 (50) patients was 59.7 (58.0) years, the mean disease duration was 10.8 (10.9) years, the mean DAS28-ESR was 4.8 (4.8), and 37.7 (36.0) % of patients were taking concomitant MTX. At one year, the mean change from baseline in van der Heijde-modified total Sharp score (mTSS) was 0.79 (0.57), and the structural remission rate (ΔmTSS≤0.5) was 69.2 (68.6) %. Neither disease duration nor concomitant MTX affected the structural remission rate at one year. The structural remission rate for 3 years (ΔmTSS≤1.5) was 66.0%, however, the mean change from 1 to 2 years in mTSS was 0.10, and that from 2 to 3 years was 0.02. Consistent with the yearly progression, the structural remission rate from 1 to 2 years was 78.6%, and that from 2 to 3 years was 88.9%, indicating that TCZ strongly and continuously inhibited radiographic progression. Image/graph: Conclusions: Long-term administration of TCZ increased the structural remission rate year by year and continuously inhibited structural joint damage in RA patients under routine clinical practice. References: Hirabayashi Y, Ishii T, and the Michinoku Tocilizumab Study Group. The DAS28-ESR cutoff value necessary to achieve remission under the new Boolean-based remission criteria in patients receiving tocilizumab. Clin Rheumatol. DOI 10.1007/s10067-012-2103-4. Disclosure of Interest: R. Watanabe: None Declared, H. Okuno: None Declared, T. Ishii Speakers bureau: Chugai Pharma, H. Harigae Grant/research support from: Chugai Pharma, Y. Hirabayashi Speakers bureau: Chugai Pharma